Research of Harmonic Minimization Possibilities in Grid-tied Photovoltaic System - Ramonas, C.; Adomavicius, V.; Gecys, S. (Elektronika ir Elektrotechnika, 2011)
The photovoltaic power systems are becoming important in the power production market with each succeeding year what can be determined by the skyrocketing development of cumulative installed power of the PV installations in the EU countries and worldwide. In this paper results of researches for minimization of the total current and voltage harmonics’ distortion of the PV system are presented. Researches were performed by means of MATLAB/SIMULINK programme and “Powerqui“ unit. Method for minimization of electromagnetic disturbances generated by the small scale PV system is based on the selection of the proper shape and parameters of the modulation voltage. Two shapes of the modulation voltage are proposed: the curve of sine voltages of first and third harmonics and the curve of the sine voltage involutes in the n power. Dependences of the total harmonic disturbances of the inverted current and voltage on the parameters of proposed forms of modulation voltage were determined by means of simulation. Evident extreme values of the total harmonic disturbances (minimums) at certain varied parameters were found in both cases. According to the results of researches the curve of sine voltages of first and third harmonics proved itself as giving twice less total harmonic disturbances of inverted current. Total harmonic disturbances of the inverted voltage show that its dependence of the on the form and parameters of modulation voltage is not so sensitive.